ENT 530 Social Media Portfolio: Popia By Sibling / Nur Farhanah Mohamed Faizal - Mohamed Faizal, Nur Farhanah (2021)
Popia By Siblings is a partnership business that are owned by two siblings named Miss Farhanah and Miss Farisah. They sell two main foods which are Popia Carbonara and Garlic Cheese Bun. Their aim is to offer food with cheap price but also made in high quality ingredients. Other than that, they also strive to provide fast service in the aspects of delivery and customer service. They started their business on 20th of June 2020. According to the customers’ feedback, they love Popia Carbonara from Popia By Siblings because it has a lot of carbonara sauce and the Popiah Skin is really crispy. Not only that, it is also sold in cheap price. Popia By Siblings are expanding their business through online platforms such as Facebook and Instagram. Their goal is to reach more customers and increase brand awareness.